2021
DOI: 10.1177/09544062211012711
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of part motion on a linear vibratory feeder

Abstract: The motion of a part on a curved surface mounted upon a linear vibratory feeder is of great importance in mass production. In this article, the conveying surface or track is modelled by a bilinear surface inclined to all axes with the curvature varying throughout the surface. An experimental test rig is fabricated to study the part motion on the feeder surface. Dynamics of the part on the surface is derived and the path traced by the part is obtained numerically. The numeric model closely correlates with exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Theoretical and experimental investigations have shown that the theory of a material point moving on a vibrating surface with dry friction describes with sufficient accuracy the process of vibratory conveying of piece products [2,[13][14][15][16]. This paper continues the previous author's study [7,12], where the vibratory conveying with longitudinal harmonic and polyharmonic normal oscillations was considered.…”
Section: Equations Of the Motion Of A Materials Point On The Vibratin...supporting
confidence: 55%
“…Theoretical and experimental investigations have shown that the theory of a material point moving on a vibrating surface with dry friction describes with sufficient accuracy the process of vibratory conveying of piece products [2,[13][14][15][16]. This paper continues the previous author's study [7,12], where the vibratory conveying with longitudinal harmonic and polyharmonic normal oscillations was considered.…”
Section: Equations Of the Motion Of A Materials Point On The Vibratin...supporting
confidence: 55%
“…Researchers have explored the stick-slip phenomenon that occurred during the conveying of parts in vibratory motion (Mayyas, 2021). A study on the dynamics of part motion on linear vibratory feeders is essential aspect in determining the part orientation and design of trap module (Balaji et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In this case the authors have modelled the part motion on a parametric surface and validated the results. 18 The path can also be curved in instances where the parts were conveyed in a rotating unit with blades. 19 But in a bowl feeder the part motion is always curved as the part moves up a spiral track.…”
Section: Introductionmentioning
confidence: 99%